Bug Propagation through Code Cloning: An Empirical Study - Mondal, Manishankar; Roy, Chanchal K.; Schneider, Kevin A. (ICSME 2017 : proceedings : 2017 IEEE International Conference on Software Maintenance and Evolution : 19-22 September 2017, Shanghai, China, 2017)
Code clones are defined to be the identical or nearly similar code fragments in a code-base. According to a number of existing studies, code clones are directly related to bugs and inconsistencies in software systems. Code cloning (i.e., creating code clones) is suspected to propagate temporarily hidden bugs from one code fragment to another. However, there is no study on the intensity of bug-propagation through code cloning.In this paper we present our empirical study on bug-propagation through code cloning. We define two clone evolution patterns that reasonably indicate bug propagation through code cloning. We first identify code clones that experienced bug-fix changes by analyzing software evolution history, and then determine which of these code clones evolved following the bug propagation patterns. According to our study on thousands of commits of four open-source subject systems written in Java, up to 33% of the clone fragments that experience bug-fix changes can contain propagated bugs. Around 28.57% of the bug-fixes experienced by the code clones can occur for fixing propagated bugs. We also find that near-miss clones are primarily involved with bug-propagation rather than identical clones. The clone fragments involved with bug propagation are mostly method clones. Bug propagation is more likely to occur in the clone fragments that are created in the same commit operation rather than in different commits. Our findings are important for prioritizing code clones for refactoring and tracking from the perspective of bug propagation.